Evaluation of African cultivated rice Oryza glaberrima for resistance to bacterial blight - Djedatin, Gustave; Ndjiondjop, Marie-Noëlle; Mathieu, Thierry; Vera Cruz, Casiana M.; Sanni, Ambaliou; Ghesquière, Alain; Verdier, Valérie (Scientific Societies, 2011)
Xanthomonas oryzae pv. oryzae is the causal agent of bacterial blight in rice, one of the most devastating diseases of rice worldwide. African X. oryzae pv. oryzae strains belong to a clear genetic group distinct from those of Asia. Three new races of the pathogen were characterized among strains from West Africa. We evaluated 107 Oryza glaberrima accessions for resistance to bacterial blight under greenhouse conditions. Six-week-old seedlings were inoculated with five different African X. oryzae pv. oryzae strains originating from the West African nations of Burkina and Mali and representing different races (A1, A2, and A3). Philippine X. oryzae pv. oryzae strain PXO86 (race 2) was also used. Most (48%) of the accessions of O. glaberrima were highly susceptible to X. oryzae pv. oryzae strains from Burkina, while 20 and 36 were resistant to X. oryzae pv. oryzae strains from Mali and the Philippines, respectively. CAPS markers and dot blot assays were used for detection of resistance genes xa5 and Xa21 from a selected set of O. glaberrima accessions. Our results suggest that the O. glaberrima germplasm contains a narrow genetic base for resistance to X. oryzae pv. oryzae. Sources of resistance identified among O. glaberrima are recommended for rice breeding programs to develop bacterial blight-resistant cultivars for West Africa.